1979
DOI: 10.1002/jhet.5570160301
|View full text |Cite
|
Sign up to set email alerts
|

3(2H)Furanone derivatives. Ring‐chain tautomerism in the 1,3,4,6‐tetraketone series

Abstract: Ring‐chain tautomeric equilibria in the 1,3,4,6‐tetraketone series 1 have been examined and the identification of the chain‐form 2 and hydroxyfuranone 3 has been accomplished from 1H‐nmr spectra; the relative contribution of the two depends on the structure and also on the solvent. Conversions of 1 into 3(2H)furanones 4 and 5 involving the cyclic tautomer 3 are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…A similar type of ring-chain tautomerism was observed [458] in the series of 1,6-disubstituted 1,3,4,6-hexanetetrones (136A) ~ (136B). Both forms of the diphenyl derivative (136, R I = R2 = Ph) have been isolated: a yellow chelate (136A) and a colorless cyclic 2-hydroxy-2-phenacyl-5phenyl-3(2H)furanone (136B).…”
Section: Cy(supporting
confidence: 72%
“…A similar type of ring-chain tautomerism was observed [458] in the series of 1,6-disubstituted 1,3,4,6-hexanetetrones (136A) ~ (136B). Both forms of the diphenyl derivative (136, R I = R2 = Ph) have been isolated: a yellow chelate (136A) and a colorless cyclic 2-hydroxy-2-phenacyl-5phenyl-3(2H)furanone (136B).…”
Section: Cy(supporting
confidence: 72%
“…[6] Instead, there is a fast proton exchange between diketodienediols (a) and 2-hydroxy-2-acylmethyl-3(2H)-furanone (the minor tautomer). [6] 1,4-Di-(pyridin-2-yl)-2,3-butanedione is the diimine derivative of the respective 1,3,4,6-tetraone. These two compounds are isoelectronic.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Balenovic andP oje first studied the tautomerism of various1 ,3,4,6-tetraketones in solution by means of NMR spectroscopy. [15] They realized that the molecular structure and ratio of the tautomers presentw ere strongly solvent dependent. In deuterated chloroform, they exclusively observed the bis-enol structure 1c.A ll possible keto-enol tautomers 1ac and mosti nterestingly the semiacetal 1d,p roduct of ar ing-chain tautomerism, were observed in deuterated dimethyl sulfoxide ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…In deuterated chloroform, they exclusively observed the bis-enol structure 1c.A ll possible keto-enol tautomers 1ac and mosti nterestingly the semiacetal 1d,p roduct of ar ing-chain tautomerism, were observed in deuterated dimethyl sulfoxide ( Figure 1A). [15][16]17] The multiplicity of coexisting isomeric structures was extended when Noe et al [18] andH art [19] independently reported 1,3,4,6-tetracarbonyl 2 derivedf rom natural occurring (+ +)-(R)camphor.Both reported the simultaneous presence of structurally related isomers that cannot be rationalized by any tautomerism known so far.H art postulated six possible structures differing in the enol protons positiona nd an s-cis/s-trans isomerism of the central single bond and suggested 2 s-trans and 2 s-cis ( Figure 1B)a st he most probable structures in solution. In the context of our investigations of controllable molecular systems that can coexisti ns everali nterconverting states, [20][21][22][23] we becamea ware of this unexplained phenomenon.…”
Section: Introductionmentioning
confidence: 99%